Two-dimensional hysteresis comparators to control multistage inverters with maximum number of levels - Menshawi, M.K.; Kadir, M.N.A.; Mekhilef, Saad (2011)
Specially designed two-dimensional hysteresis comparators have been proposed to replace the algebraic calculations to control multistage inverter designed with maximum number of levels. The inverter is operated to approximate the reference voltage vector exploiting the large number of multilevel inverter vectors. Three-stage inverter with singly-fed main stage is considered to apply the proposed design. The controller concept is to maintain the higher voltage stage state as long as this state can lead to the target vector. The high and medium voltage stages controllers are based on two-dimensional hysteresis comparators to hold the switching state or to perform the necessary change with minimum switching losses. The low voltage stage controller is designed to approximate the reference voltage to the nearest inverter vector using nearest integer rounding and adjustment comparators. Simulation and experimental results show that the proposed controller outperforms the previous control methods in terms of simplicity, harmonics reductions and robustness.